Міфорелігійний простір повсякденної реальності українських носіїв православної свідомості - Борейко, Юрій Григорович; Борейко, Юрий Григорович; Boreiko, Yurii H. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано сферу сучасного міфорелігійного простору в контексті життєвого світу українських носіїв буденної православної свідомості. Міфорелігійний простір визначено як область мозаїчних локусів, у яких кожен із компонентів функціонує в рамках суб’єктивного розуміння релігійної істини та його призначення. Специфічною рисою цього простору є використання міфологем як для конструювання повсякденної реальності, так і для її руйнування. Установлено, що маси населення через звернення до міфологем намагаються знайти почуття особистої та колективної самоцінності, міфотворці ж, апелюючи до почуттів, прагнуть соціального контролю. The article analyzes the scope of modern mythological and religious space in the context of the living world Ukrainian carrier of orthodox everyday consciousness. Mythological and religious space is defined as an area of mosaic loci in which each component operates in the subjective understanding of religious truth and its purpose. A specific feature mythological and religious space is to use myths to construct everyday reality. The modern myth is one of the factors that determine the mass consciousness and a tool to influence them through designing religious myths and ideologies. In modern society, the impact on public consciousness occurs, including also through religious myth, which leads to structural changes modern mythological and religious space. Mythology consciously constructed and updated in the context of mythologizing, which eliminates part of the myth and narrative focuses on a streamlined categories and principles. The process of mythologizing is a constant, continuous and comes to interpreting the world within a world, so a change in ideas and concepts come to others that society plays as a value.
Mythological and Religious Space of Everyday Reality of Ukrainian Carriers of Orthodox Consciousness
Keywords: міфорелігійний простір; повсякденна реальність; буденна свідомість; міфологема; православна свідомість; релігійна повсякденність; mythological and religious space; everyday reality; everyday consciousness; myth; orthodox consciousness; religious routine